2003
DOI: 10.1093/jjco/hyg051
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Pharmacokinetic Study of KRN5500, a Spicamycin Derivative, for Patients with Advanced Solid Tumors

Abstract: KRN5500, a structurally novel protein synthesis inhibitor, warrants further investigation to overcome these toxicity profiles and improve its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The possible mechanism is that KRN5500 might modulate the cell surface saccharides and inhibit adhesion of osteoclasts, which results in the decreased number of mature osteoclasts in vitro and in vivo . In previous clinical trials of KRN5500, adverse events related to osteoclast inhibition were not reported in patients with solid tumours (Takama et al , 2001; Supko et al , 2003; Yamamoto et al , 2003) although the concentrations of KRN5500 in in vitro experiments were at clinically achievable levels. Therefore, there is a possibility that this inhibition is specific for activated osteoclasts in the bone marrow environment of MM patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The possible mechanism is that KRN5500 might modulate the cell surface saccharides and inhibit adhesion of osteoclasts, which results in the decreased number of mature osteoclasts in vitro and in vivo . In previous clinical trials of KRN5500, adverse events related to osteoclast inhibition were not reported in patients with solid tumours (Takama et al , 2001; Supko et al , 2003; Yamamoto et al , 2003) although the concentrations of KRN5500 in in vitro experiments were at clinically achievable levels. Therefore, there is a possibility that this inhibition is specific for activated osteoclasts in the bone marrow environment of MM patients.…”
Section: Discussionmentioning
confidence: 94%
“…This pathway is not a target for conventional chemotherapeutic agents, and therefore KRN5500 is expected to be a unique compound for the treatment of neoplastic diseases (Lee et al , 1995; Kamishohara et al , 1996; Kawasaki et al , 2000; Stine et al , 2000; Zhang et al , 2000; Byrd et al , 2003). Several phase I studies of KRN5500 have been conducted in patients with solid tumours showing acceptable toxicity with Cmax values of 1000–3000 nmol/l (Takama et al , 2001; Supko et al , 2003; Yamamoto et al , 2003). However, these studies showed that KRN5500 induced little anti‐tumour response; therefore, no further trials were done in patients with solid tumours.…”
mentioning
confidence: 99%